Cyberbulling no espaço escolar : uma interpretação do fenômeno no âmbito da Educação Física - Brandão, Cirlei da Aparecida (2014)
This study aimed to construe the situations of violence among students from 6th to 9th grade of Elementary School in form of bullying and cyberbullying as part of physical education, in order to produce data as guidelines for future educational intervention programs in the area. With this goal, we performed a bibliographic survey that showed conceptual aspects, origin, causes of violence and school violence. We also discussed bullying and cyberbullying variant in the ambience of Physical Education, incidence, causes, manifestations, distinctions, profile of protagonists as well as their consequences. The methodology adopted was the case study, qualitative and quantitative research with a phenomenological perspective, with the universe for a particular school in Mato Grosso, being subject 119 elementary school students, from 6th to 9th grade, whose ages were between 10 through 15 years, physical education teachers and other disciplines, management and technical staff. Survey on SurveyMonkey platform was used as on line research tool, answered by the students. Another survey instrument used was the technique of focus groups with students, teachers and management team, whose model was an interpretive analysis. It was found in the ambience of physical education when classes prioritize competition, it is a facilitator of bullying occurrence, which can be unleashed on cyberbullying, environment, and that in most cases, neither the school nor the teachers are told, so appropriate attitudes are not taken.